Microstructure engineering of metamagnetic Ni-Mn-based Heusler compounds by Fe-doping: A roadmap towards excellent cyclic stability combined with large elastocaloric and magnetocaloric effects. (December 2021) - Pfeuffer, Lukas; Lemke, Jonas; Shayanfar, Navid; Riegg, Stefan; Koch, David; Taubel, Andreas; Scheibel, Franziska; Kani, Nagaarjhuna A.; Adabifiroozjaei, Esmaeil; Molina-Luna, Leopoldo; Skokov, Konstantin P.; Gutfleisch, Oliver
Abstract: Ni-Mn-based metamagnetic shape-memory alloys exhibit a giant thermal response to magnetic fields and uniaxial stress which can be utilized in single caloric or multicaloric cooling concepts for energy-efficient and sustainable refrigeration. However, during cyclic operation these alloys suffer from structural and functional fatigue as a result of their high intrinsic brittleness. Here, we present based on Fe-doping of Ni-Mn-In a microstructure design strategy which simultaneously improves cyclic stability and maintains the excellent magnetocaloric and elastocaloric properties. Our results reveal that precipitation of a strongly Fe-enriched and In-depleted coherent secondary γ-phase at grain boundaries can ensure excellent mechanical stability by hindering intergranular fracture during cyclic loading. In this way, a large elastocaloric effect of -4.5 K was achieved for more than 16000 cycles without structural or functional degradation, which corresponds to an increase of the cyclic stability by more than three orders of magnitude as compared to single-phase Ni-Mn-In-(Fe). In addition, we demonstrate that the large magnetocaloric effect of single-phase Ni-Mn-In-(Fe) can be preserved in the dual-phase material when the secondary γ-phase is exclusively formed at grain boundaries as the martensitic transformation within the Heusler matrix is barely affected. This way, an adiabatic temperature change of -3 K and an isothermal entropy change of 15 Jkg −1 K −1 was obtained in 2 T for dual-phase Ni-Mn-In-Fe. We expect that this concept can be applied to other single caloric and mutlicaloric materials, therewith paving the way for solid-state caloric cooling applications. Graphical abstract: Image, graphical abstract